Ion selectivity of scorpion toxin-induced pores in cardiac myocytes - Elgar, Dale; Verdonck, Fons; Grobler, Anne; Fourie, Carla; du Plessis, Johan (Peptides (New York, N.Y. : 1980), 2006)
The lytic activity of parabutoporin (PP) and opistoporin 1 (OP1) on mammalian and bacterial membranes have been described. We investigated pore-formation and ion selectivity in cardiac myocytes by measuring the whole cell leak current by means of the patch clamp technique. Pore formation was observed as the induction of leak currents. Ion selectivity of the pores was indicated by the shift of the reversal potential ( E rev) upon substitution of intra- and extra-cellular ions. Results were compared with the effect of gramicidin A (gramA). PP and OP1 induced a fluctuating leak current and indicate non-selectivity of PP-induced pores. PP- and OP1-induced pores are between 1.38 and 1.78 nm in diameter.